2019
DOI: 10.5038/2640-6489.4.1.1041
|View full text |Cite
|
Sign up to set email alerts
|

The effect of website quality on repurchase intention with the mediation of perceived value: The case study of online travel agencies in Vietnam

Abstract: The sharing economy is getting broader with its non-ownership assets, better use of resources, lower prices, and more customized products (Belk, 2014). In tourism industry, the development of the sharing economy involved the emergence of online travel agencies (OTAs) who are intermediates between services providers and consumers, provide accommodations, transport services, food and beverages services, tour guide services, etc. (Skalska, 2017). Recently, Vietnam has experienced a rapid growth in the number of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 54 publications
7
27
1
10
Order By: Relevance
“…Finally, the study established that brand image has a significant direct influence on perceived value in the OTC herbal market. This outcome is similar to the earlier studies (Pham & Nguyen, 2019;Lien et al, 2015), which report that favourable brand image directly affects the perceived value. However, this result differs from the study of prior authors (Chung, Yu, Kim & Shin, 2015;Yan, 2019), who found that enhanced perceived value enhances the image of brands.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Finally, the study established that brand image has a significant direct influence on perceived value in the OTC herbal market. This outcome is similar to the earlier studies (Pham & Nguyen, 2019;Lien et al, 2015), which report that favourable brand image directly affects the perceived value. However, this result differs from the study of prior authors (Chung, Yu, Kim & Shin, 2015;Yan, 2019), who found that enhanced perceived value enhances the image of brands.…”
Section: Discussionsupporting
confidence: 91%
“…The author further noted that brand image provides the basis for purchase decision and a source of customer satisfaction. Empirical studies also established that brand image has a direct effect on perceived value (Pham & Nguyen, 2019;Lien, Wen, Huang, & Wu, 2015;Huang et al, 2019).…”
Section: Brand Imagementioning
confidence: 99%
See 2 more Smart Citations
“…To realize repeat purchases, e-commerce needs to increase customer interest to continue using their e-commerce platform. Repurchase intention is the customers willingness to buy products or services both online and offline based on the benefits they have felt (Pham & Nguyen, 2019). Online repurchase intention will increase if it is match to customer perceptions towards products, likewise to online facilities offered by e-commerce Customer perceived value is the evaluation felt by customers of all the benefits and costs offered by the seller/store (Kotler & Keller, 2018).…”
Section: Theoretical Reviewmentioning
confidence: 99%